PEMBUKUAN KEUANGAN BERBASIS DIGITAL MENGGUNAKAN APLIKASI BUKU KAS - Nur Jannah; Rafika Rahmawati; Siti Mardiah; Mas Deden Tirtajaya; Arief Widyananto (LPPM Universitas Islam 45, 2023)
There are several UMKM food stalls in Rawa Pasung village rt.rw 001/004 that have not recorded transactions in the books this is due to a lack of knowledge of the importance of financial management, as well as lack of skills in operating bookkeeping through digital applications. Based on these problems, KKN participants want to help introduce digital-based bookkeeping which is supported by the emergence of software that can be used to do bookkeeping using a digital-based application, namely the cash book application. This activity was attended by five participants with the methods of discussion and education, socialization, training and evaluation. With the aim of MSME actors in Rawa Pasung Village being able to practice business bookkeeping using a cash book application so that they can monitor their finances quickly and accurately. This Real Work Lecture activity has been carried out since February 7, 2022 - March 4, 2022. The results of these activities have a very positive impact on the business finances of the shop owners to increase knowledge and innovation in doing bookkeeping and are interested in using this digital application for the long term because This cash book application makes it easy for shop owners to record anytime and anywhere.